Clinical practice guideline on prevention of rhabdomyolysis induced acute kidney injury: Endorsement by the Scandinavian Society of Anaesthesiology and Intensive Care Medicine. Issue 10 (9th September 2019) - Chew, Michelle S.; Rehn, Marius; Olkkola, Klaus T.; Örn Sverrisson, Kristinn; Yli‐Hankala, Arvi; Møller, Morten Hylander
Abstract : The Scandinavian Society of Anaesthesiology and Intensive Care Medicine Clinical Practice Committee endorses the recent DASAIM/DSIT guideline for prevention of rhabdomyolysis‐induced acute kidney injury . However, we emphasize the low quality of evidence with only weak recommendations for all interventions, highlighting that further research is very likely to have an important impact on the confidence in the estimate of effect and is likely to change the estimates.